Clinical outcomes with reservoir‐based polymer‐free amphilimus‐eluting stents in real‐world patients according to diabetes mellitus and complexity: The INVESTIG8 registry. Issue 5 (14th July 2017) - Sardella, Gennaro; Stella, Pieter; Chiarito, Mauro; Leone, Antonio M.; Balian, Vruyr; Prosperi, Franco; Sorropago, Giovanni; Mancone, Massimo; Calcagno, Simone; Briguori, Carlo; Stefanini, Giulio G.
Abstract: Background: Patients with diabetes mellitus (DM) remain at higher risk of restenosis after percutaneous coronary intervention despite the use of contemporary drug‐eluting stents. The Cre8 amphilimus‐eluting stent (AES) has shown promising results in DM patients. Whether this holds true irrespective of patient's clinical and angiographic complexity is unknown. Methods: Five hundred and ninety five consecutive patients (738 lesions) undergoing AES implantation were included in the INVESTIG8 multicenter registry. Patients were stratified according to DM status and further stratified according to patients' complexity. The prespecified primary endpoint was target lesion failure (TLF)–defined as the composite of cardiac death, target‐vessel myocardial infarction, and target lesion revascularization (TLR). Results: DM patients were more often complex as compared to non‐DM patients (70% vs. 61%, P  = 0.015). At 18‐month follow‐up, there was a trend to a higher TLF rate in DM than in non‐DM patients (6.9% vs. 3.5%, P  = 0.063). This was largely driven by a markedly higher risk of TLF among complex DM patients as compared to simple DM patients (8.9% vs. 2.4%, P  = 0.053). A multivariate analysis identified complexity (HR 6.11, 95% CI: 1.42–26.2) but not DM (HR 1.59; 95% CI 0.71–3.56) as an independent predictor of TLF. Of note, TLR rates were similar between DM and non‐DM patients (3.3% vs. 1.9%, P  = 0.228). Conclusions: In this real‐world, multicenter registry the Cre8 AES showed favorable clinical outcomes in DM patients. Increased risk of TLF appears to be driven by patients' complexity rather than DM status. These findings will need to be confirmed in a large‐scale randomized trial.